2014
DOI: 10.1016/j.neuro.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of trimethyltin injury in the rat brain using magnetic resonance histology

Abstract: The growing exposure to chemicals in our environment and the increasing concern over their impact on health have elevated the need for new methods for surveying the detrimental effects of these compounds. Today’s gold standard for assessing the effects of toxicants on the brain is based on hematoxylin and eosin (H&E)-stained histology, sometimes accompanied by special stains or immunohistochemistry for neural processes and myelin. This approach is time-consuming and is usually limited to a fraction of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Furthermore, what we have demonstrated here is that this neuroinflammatory response results in subtle, but differentiable changes in diffusion MRI, which highlights the ability to detect inflammatory-induced changes in MRI patterns early and without the requirement of severe damage to the brain tissue. Recent studies using similar diffusion parameters also reported successful discrimination of microstructural changes in neuronal or glial cell elements (Johnson et al, 2014, Blumenfeld-Katzir et al, 2011). In addition, high-order diffusion MRI successfully captured statistically significant changes in diffusion indices in a rat model of mild traumatic brain injury as early as 2 h post-injury (Zhuo et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, what we have demonstrated here is that this neuroinflammatory response results in subtle, but differentiable changes in diffusion MRI, which highlights the ability to detect inflammatory-induced changes in MRI patterns early and without the requirement of severe damage to the brain tissue. Recent studies using similar diffusion parameters also reported successful discrimination of microstructural changes in neuronal or glial cell elements (Johnson et al, 2014, Blumenfeld-Katzir et al, 2011). In addition, high-order diffusion MRI successfully captured statistically significant changes in diffusion indices in a rat model of mild traumatic brain injury as early as 2 h post-injury (Zhuo et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…In rats exposed to TMT orally, early swelling and thickening of the optic fiber layer were observed in some segments of the retina (Chang and Dyer, 1983b). In addition, intraperitoneal exposure of rats to TMT resulted in changes in white matter regions of their brains, including the fimbria and corpus callosum, as well as hippocampal neuron, on diffusion tensor images (Johnson et al 2014). All these findings suggest that white matter lesions can be observed in TMT intoxication.…”
Section: Discussionmentioning
confidence: 85%
“…In GFA mapping, the left middle frontal gyrus ROI (#213) in the curcumin group revealed significant pattern differences against the controls. In previous studies, it has been shown that the impact of aging in area 46 (overlaps to #213), is likely due to loss of dendritic arborization or synaptic integrity (reviews for Peters and Kemper, 2012), which can decrease complexity in the medium and enhance either radial or tangential diffusion components (Johnson et al, 2014; Zhuo et al, 2012). If this is the case, then lowered GFA in the frontal cortex of curcumin treated animals can be postulated as an increased complexity due to intactness of subneuronal components.…”
Section: Discussionmentioning
confidence: 99%